Die Zukunft des Deutschen MeSH: Vom Übersetzungsprozess zum Terminologie-Service - Wollnik-Korn, Gabriele; Fischer-Wagener, Brigitte; Langnickel, Lisa; Schneider, Julian; Baum, Roman; Fluck, Juliane (GMS Medizin – Bibliothek – Information, 2020)
The poster outlines which services and goals ZB MED has set itself by assuming responsibility for the German MeSH, the current status, future tasks and the relevance of the professional community in setting up our services. This poster addresses the translation process of the German MeSH 2020 and the developed software prototype.ZB MED is ideally suited to guarantee the future maintenance of German translations of the Medical Subject Headings (MeSH), thus creating the conditions for the consistent use of medical terminology in the German-speaking world.